In situ Measurement of Phosphate using Fe3O4/Chelex®100-Agarose-Oxalic Acid Hydrogel in Diffusive Gradient in Thin Films - Dinira, Layta; Rumhayati, Barlah; Mardiana, Diah; Andayani, Ulfa (Molekul, 2024)
ABSTRACT. This study would be the first to develop a novel combination of Chelex®100 and Fe3O4 as a mixed binding gel for in situ phosphate measurement employing Diffusive Gradient in Thin Films (DGT). Fe3O4 and Chelex®100 were utilized as binding agents within a single binding layer for phosphate measurements in laboratory and natural water settings. The synthesized Fe3O4 was identified as magnetite and consisted of micro-sized particles. The pore size of the mixed binding gel ranged from 22.39 to 112.5 µm. Incorporating Chelex®100 with Fe3O4 in oxalic acid cross-linked agarose did not diminish phosphate adsorption efficiency. As adsorption time and phosphate concentration in solution increased, the quantity of adsorbed phosphate in the mixed binding gel also increased. Optimal phosphate elution was achieved using a basic solution, with a phosphate elution efficiency of 95.3 ± 0.4% observed with 0.4 M NaOH. The diffusion coefficient measured using the mixed binding gel was 1.08 times greater than that of polyacrylamide cross-linked with an agarose derivative (APA) gel, typically employed in the DGT technique. Phosphate concentration measurement with Fe3O4/Chelex®100-agarose oxalic acid in a DGT passive sampler at pH 4-8 yielded values twice those in bulk solution. Similar results were obtained when measuring phosphate in a 0.01 – 0.1 M NaNO3 solution. A T-test showed that the phosphate concentration obtained from mixed binding layer-DGT as an alternate passive sampler was not significantly different from grab sampling. This study underscores the suitability of Fe3O4-Chelex®100 impregnated in agarose-oxalic acid gel for monitoring phosphate in natural water via DGT. Keywords: Agarose, diffusive gradient in thin films, mixed binding gel Fe3O4, oxalic acid.